Performance of nanoceramic powder on the chemical and physical properties of bitumen - Abdulameer Hussein, Ahmed; Putra Jaya, Ramadhansyah; Abdul Hassan, Norhidayah; Yaacob, Haryati; Huseien, Ghasan Fahim; Wan Ibrahim, Mohd Haziman (Elsevier Science Ltd, 2017)
Approximately 30% of industrially produced ceramic materials worldwide are dumped as waste in land-ﬁlls. Thus, these materials are a major environmental concern. Reusing or recycling these ceramic wastes for constructive purposes remains challenging. In this work, we evaluated for the ﬁrst time the modiﬁed chemical and physical properties of bitumen incorporated with inorganic nanoceramic powder (NCP) produced from the ceramic wastes. Chemical and morphological properties of bitumen with NCP were determined. Bitumen specimens were characterized using transmission electron microscopy, X-ray ﬂuo-rescence spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and atomic force microscopy (AFM). Physical and rheological properties of the specimens were also examined by penetra-tion, softening point, and dynamic shear rheometer tests. Morphological analysis revealed the formation of an interaction between the SiAOASi stretching vibration and hydrocarbon molecules. This interaction resulted from the incorporation of NCP into the unmodiﬁed bitumen matrix. The interaction increased the viscosity and reassembled the asphaltene particles. Thus, a new asphaltene sheet was generated, and the aromatic bonds (C@C) were strengthened. AFM results reafﬁrmed the structural improvement of bitumen. Furthermore, the elasticity of bitumen and viscoelasticity of its matrix increased. These improvements can be attributed to the formation of the polyaromatic structure.